2018
DOI: 10.1038/s41467-018-03476-6
|View full text |Cite|
|
Sign up to set email alerts
|

Atrx inactivation drives disease-defining phenotypes in glioma cells of origin through global epigenomic remodeling

Abstract: Mutational inactivation of the SWI/SNF chromatin regulator ATRX occurs frequently in gliomas, the most common primary brain tumors. Whether and how ATRX deficiency promotes oncogenesis by epigenomic dysregulation remains unclear, despite its recent implication in both genomic instability and telomere dysfunction. Here we report that Atrx loss recapitulates characteristic disease phenotypes and molecular features in putative glioma cells of origin, inducing cellular motility although also shifting differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 57 publications
8
79
0
1
Order By: Relevance
“…How can the anti‐proliferation response of ATRX or DAXX loss be reconciled with their tumor suppressor roles? It is important to point out that besides their crucial roles in telomere maintenance, ATRX and DAXX also participate in many other biological processes, including gene expression (Gibbons et al , ; Law et al , ; Ratnakumar et al , ; Sarma et al , ; Danussi et al , ), DNA damage repair (Koschmann et al , ; Juhasz et al , ), senescence (Kovatcheva et al , ), and regulation of chromatin state and composition (Law et al , ; He et al , ; Voon et al , ). We speculate that DAXX and ATRX may exert their tumor suppressor roles independently of their telomere maintenance function.…”
Section: Discussionmentioning
confidence: 99%
“…How can the anti‐proliferation response of ATRX or DAXX loss be reconciled with their tumor suppressor roles? It is important to point out that besides their crucial roles in telomere maintenance, ATRX and DAXX also participate in many other biological processes, including gene expression (Gibbons et al , ; Law et al , ; Ratnakumar et al , ; Sarma et al , ; Danussi et al , ), DNA damage repair (Koschmann et al , ; Juhasz et al , ), senescence (Kovatcheva et al , ), and regulation of chromatin state and composition (Law et al , ; He et al , ; Voon et al , ). We speculate that DAXX and ATRX may exert their tumor suppressor roles independently of their telomere maintenance function.…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies linking different levels of expression of ATRX as drivers of specific phenotypes that give rise to disease and cancer [13,18,19]. In the present study, we searched human somatic cancer databases and found that the ATRX gene is overexpressed in a wide variety of human cancers.…”
Section: Introductionmentioning
confidence: 81%
“…That ATRX itself encodes a chromatin regulatory protein suggests that epigenomic dysfunction underlies, at least in part, the oncogenic sequelae of its inactivation. To this point, we recently demonstrated that ATRX deficiency induces extensive chromatin remodeling and transcriptional shifts in putative glioma cells of origin, driving disease-relevant phenotypes that modulate both cellular motility and differentiation 38 . However, the full impact of ATRX deficiency on tumor initiation and evolution almost certainly includes other molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%